Improving the hydrophobicity and mechanical properties of starch nanofibrous films by electrospinning and cross-linking for food packaging applications. (1st November 2022) - Zhu, Weijia; Zhang, Die; Liu, Xiaoqing; Ma, Tiezheng; He, Jiangling; Dong, Qi; Din, Zia-ud; Zhou, Jiaojiao; Chen, Lei; Hu, Zhongze; Cai, Jie
Abstract: Many efforts have been devoted to developing starch-based films as an alternative to non-degradable petroleum-based plastic food packaging. However, the application of starch-based films still faces serious challenges due to their water sensitivity and poor mechanical properties. In this work, a simple route was proposed to develop crosslinked starch nanofibrous films (C-SNFs) through electrospinning of starch solution, followed by crosslinking in glutaraldehyde (GTA) vapor. The effect of electrospinning parameters such as starch concentration (20–30 wt%), applied voltage (15–25 kV), and collecting distance (10–20 cm) on fiber morphology was studied. Compared with solution-cast starch films, electrospun starch nanofibrous films (SNFs) showed superior flexibility but poor mechanical strength and water sensitivity. After GTA crosslinking post-treatment, the tensile strength and water contact angle (WCA) of SNFs could be enhanced up to ∼9.65 MPa and ∼94.3°, respectively. Results from this work could provide a facile route to fabricate starch-based film materials that showed a promising potential application in the food packaging field. Graphical abstract: Pure crosslinked starch nanofibrous films with improving tensile strength and hydrophobicity Image 1 Highlights: Starch nanofibrous films (SNFs) for food packaging were improved by electrospinning and cross-linking. Smooth and bead-free starch nanofibers were optimized by varying electrospinning parameters. GTA crosslink reaction enhanced the hydrophobicity and mechanical strength of SNFs.